2020
DOI: 10.3389/fnins.2020.559117
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure Changes and Cognitive Impairment in the Progression of Chronic Kidney Disease

Abstract: Background Cognitive impairment is a well-defined complication of chronic kidney disease (CKD), but the neural mechanisms are largely unknown. Objectives The study aimed to assess white matter (WM) microstructure changes and their relationship with cognitive impairment development during CKD progression. Methods Diffusion tensor imaging (DTI) datasets were acquired from 38 patients with CKD (19 patients were at stage 3; 19 patients were at st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Impaired integrity of ILF and SLF is associated with language comprehension and attention-deficit disorders ( Wolfers et al, 2015 ; Shin et al, 2019 ). These results are similar to previous TBSS studies on CKD ( Yin et al, 2018 ; Liu et al, 2020 ), while more detailed localization information of damaged segments of fibers can be determined in our current study based on AFQ analyses. Meanwhile, these results indicated that MD and RD values are more sensitive than FA in discovering the extent of white matter microstructure vulnerability, which consistent with previous studies ( Amlien and Fjell, 2014 ; Jin et al, 2017 ; Chen H. F. et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Impaired integrity of ILF and SLF is associated with language comprehension and attention-deficit disorders ( Wolfers et al, 2015 ; Shin et al, 2019 ). These results are similar to previous TBSS studies on CKD ( Yin et al, 2018 ; Liu et al, 2020 ), while more detailed localization information of damaged segments of fibers can be determined in our current study based on AFQ analyses. Meanwhile, these results indicated that MD and RD values are more sensitive than FA in discovering the extent of white matter microstructure vulnerability, which consistent with previous studies ( Amlien and Fjell, 2014 ; Jin et al, 2017 ; Chen H. F. et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Most of the previous quantitative analyses focused on the abnormal structure of gray or white matter ( Zhang et al, 2013 ; Murea et al, 2015 ; Meurs et al, 2016 ). In recent years, more and more studies have confirmed that the integrity of white matter microstructure in ESRD patients has also changed using various analytical methods based on diffusion tensor imaging (DTI), including region of interest (ROI), voxel-based analysis (VBA), and tract-based spatial statistics (TBSS) ( Chou et al, 2013 , 2019 ; Kong et al, 2014 ; Chen et al, 2015 ; Yin et al, 2018 ; Liu et al, 2020 ). However, the location and range of decrease of white matter integrity varied differently across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that WM abnormalities may appear earlier than brain atrophy and are more sensitive to early marker (Bartzokis, 2011;Metzler-Baddeley et al, 2019). In addition, more severe CKD may lead to more severe WM damage, which is associated with cognitive impairment (Liu et al, 2020). Therefore, WM integrity may be a more suitable biomarker for brain changes in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the changes in WM integrity of patients with non-end-stage CKD (NES-CDK) are still limited. So far, only one study by Liu et al (Liu et al, 2020) revealed that adult patients with CKD at stage 4 have reduced integrity of WM tracts in the corpus callosum (CC), anterior thalamic radiation (ATR), inferior fronto-occipital fasciculus (IFOF), and inferior longitudinal fasciculus (ILF). To rule out the effects of long-term hemodialysis, their study only included patients with CKD at stages 3-4.…”
Section: Introductionmentioning
confidence: 99%
“…For example, post-mortem tissue, particularly from young patients, is difficult to obtain and thus resulted in a small number of available subjects for comparison. The post-mortem tissue was obtained from individuals who died of non-neurological causes and had no overt abnormalities on qualitative assessment but could have been affected by systemic problems: one of the individuals died from chronic renal failure, which has been associated with white matter abnormalities on DTI, albeit in an older population 33 . Other factors may have affected the comparison of histology and imaging.…”
Section: Discussionmentioning
confidence: 99%